Towards Personal Data Protection in Structural Leadership Training: An Analysis of Maqāshid al-Sharī'ah Perspective - Sandiza, Miftahul Heldra; Rosadi, Sinta Dewi; Suparman, Rahmat (Fakultas Syariah UINSI Samarinda, 2024)
This article discusses the Maqāshid al-Sharī'ah approach to protecting personal data in the context of structural leadership training. Maqāshid al-Sharī'ah, as a framework of Islamic legal principles, provides a strong foundation for understanding and implementing personal data protection in leadership training. This article elucidates how the training institution can incorporate measures to safeguard participants’ personal data in leadership structural training in accordance. This study employs a normative legal approach, scrutinizing the personal data protection act and structural leadership training maintenance guidelines through qualitative prescriptive research methods. It collects data from observations and relevant reference documents and employs deductive data analysis techniques. The results of this study indicate that implementing these principles requires strict policies, sophisticated security technology, staff training, and awareness about the importance of personal data. By considering the alignment between data protection and Maqāshid al-Sharī'ah, this research aims to contribute to a more robust data governance framework within leadership development programs. To implement this protection, the contribution of an officer who can serve as a data protection officer for participants in structural leadership training is required.